Improving Skills, Question Types and Techniques in Reading - Niyozmatova Oygul (Journal of Innovation in Education and Social Research, 2023)
Reading skills are abilities which relate to a person’s interest to read, understand, and interpret and desipher in written language and texts. These skills can be highly profitable to absorbing and responding to written communications like such letters, messages, emails and another written things.The most significant purpose of reading techniques is boosting comprehension of the text. Reading question types are helpful way to ensure our results and how you catch the meaning of text in reading. Reading techniques are the method how to comprehend, answer the question types and achieve enough speed in reading activities. The major purpose of this article is to present helpful hints to increase reading skills, techniques and question types. Such as being more experienced in reading skills.